2010
DOI: 10.1007/s00168-010-0367-7
|View full text |Cite
|
Sign up to set email alerts
|

Zipf’s and Gibrat’s laws for migrations

Abstract: This paper analyses the evolution of the size distribution of the stock of emigrants in the period 1960-2000. Has the distribution of the stock of emigrants changed or has there been some convergence? This is the question discussed in this work. In particular, we are interested in testing the fulfillment of two empirical regularities studied in urban economics: Zipf's law, which postulates that the product between the rank and size of a population is constant; and Gibrat's law, witch states that growth rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…In keeping with the findings of Clemente et al. (), we find, at least across most of the distribution of the stock of immigrants, that Gibrat's law holds. The major exceptions are those countries in the lower end of the distribution, which tend to grow faster than the other countries in the distribution.…”
Section: Gibrat's Law In International Migrationsupporting
confidence: 92%
See 3 more Smart Citations
“…In keeping with the findings of Clemente et al. (), we find, at least across most of the distribution of the stock of immigrants, that Gibrat's law holds. The major exceptions are those countries in the lower end of the distribution, which tend to grow faster than the other countries in the distribution.…”
Section: Gibrat's Law In International Migrationsupporting
confidence: 92%
“…Both immigrant levels and densities are log‐normally distributed as was the case in Clemente et al. () . As if Gibrat's law were to hold, the resulting distributions of the relevant variables will be log‐normal, we proceed by examining whether Gibrat's law holds for our various measures of international migration.…”
Section: An Examination Of Log‐normalitymentioning
confidence: 89%
See 2 more Smart Citations
“…As mentioned above, there is a large number of studies which show the validity of Zipf's law, particularly in the upper (truncated) tail (Clemente et al, 2011;Krugman,1996a;Levy, 2009;Mansury, 2010;Rosen and Resnick, 1980). It should noted that Soo (2005) has shown that the degree of variability of Zipf's law also depends on the estimation method used: he found contrasting results using OLS or Hill 4 estimators.…”
Section: A Brief Reviewmentioning
confidence: 97%